THU0148 Asssociation of the 22 Genotype of Enhancer HS1, 2A of the IG Heavy 3′ Regulatory Region with Non Response to Dmards and Response to Rituximab in Rheumatoid Arthritis Patients. (23rd January 2014) - Tolusso, B.; Gremese, E.; Fedele, A. L.; Serone, E.; Frezza, D.; Gigante, M. R.; Nowik, M.; Canestri, S.; Carbonella, A.; Ferraccioli, G.
Abstract : Background: Several studies underline the relevance of the genetic background for the response to therapy in the Rheumatoid Arthritis (RA). Objectives: To study the polymorphism in the enhancer HS1, 2A of the Ig heavy 3′ regulatory region (IgH 3′RR-1) as a biomarker of response to therapy in different phases of RA disease. Methods: 535 RA patients were enrolled in the study, of which: A) 326 with an early RA (ERA), treated according to a tight control strategy (Methotrexate for three months, and if an incomplete response was seen after 3 months they started a combination with Tumor Necrosis Factor (TNF) blockers), B) 89 TNF-treated patients with a long-standing RA (TNF-treated LSRA) and C) 120 seropositive LSRA patients treated with Rituximab (RTX-treated LSRA), not responsive to previous DMARDs and/or TNF-blockers. Patients were genotyped for HS1, 2A enhancer polymorphism, as previously described (1 ). Diasease activity was assessed every three months according to the European League Against Rheumatism's (EULAR) criteria. Results: The polymorphism of the HS1, 2A enhancer of the 3' regulatory region respected the Hardy-Weinberg equilibrium in all the RA cohorts. The analysis of the genotype's distribution of the HS1, 2A enhancer showed a similar frequency of the 2/2 genotype in ERA patients (28.2%) compared to RTX-treated LSRA (21.7%, p=0.17 ), but lower than in TNF-treated LSRA (40.4%, p=0.03 vs ERA). Fifty percent of ERA patients reached a good-EULAR response at 3 months follow-up visit (FU) and 23% were in sustained EULAR-remission at 6 months FU. The percentage of good-EULAR response at 3-months FU and sustained EULAR-remission at 6-month FU was lower in ERA patients carrying the 2/2 genotype of HS1, 2A enhancer compared with ERA patients without the 2/2 genotype (good-EULAR response: 35.9% vs 56.4%, OR(95%CIs): 0.43 (0.24-0.78); sustained EULAR-remission: 12.5% vs 26.1%, OR(95%CIs): 0.40 (0.18-0.91), respectively). Moreover, ERA patients carrying the 22 genotype were characterized by a more severe disease at baseline and by a higher percentage of subjects treated with TNF-blockers at 6 months FU compared to patients without the 22 genotype (26.1% vs 12.2%, p=0.01 ). In the cohort of TNF-treated LSRA patients (good-EULAR response: 32.6%) there was no association between the HS1, 2A enhancer polymorphism and the response to therapy over time. The 25% of RTX-treated LSRA patients reached a good-EULAR response at 6 months FU. The percentage of good-EULAR response was more prevalent in RTX-treated LSRA patients carrying the 2/2 genotype compared to subjects without the 22 genotype (42.3% vs 20.2%, OR (IC 95%): 2.90 (1.15-7.32)). Conclusions: The presence of the 2/2 genotype of HS1, 2A enhancer seems to identify a more aggressive disease in ERA patients poorly responsive to DMARDs and it associates to a good EULAR response to RTX in seropositive LSRA. The demonstration of the presence of a binding site for NF-kB in the allele*2 of HS12A enhancer, (2 ) could explain the more aggressive phenotype. References: Giambra V et al., Genes 2005 Frezza D et al., Ann Rheum Dis 2012. Disclosure of Interest: None Declared